2015
DOI: 10.18410/jebmh/2015/484
|View full text |Cite
|
Sign up to set email alerts
|

A Cross Sectional Study of Prevalence and Type of Diabetic Foot Ulcers in Type 2 Diabetic Mellitus Patients

Abstract: BACKGROUND: Diabetic foot ulcers are common and estimated to affect 15% of all diabetics. In India it is estimated that approximately 40,000 legs are being amputated every year of which 75% are potentially preventable. METHODOLOGY: To determine the prevalence of diabetic foot ulcers and the type of ulcers amongst the diagnosed diabetes mellitus patients a prospective study was carried out during the period January 2013 to December 2014 in the department of General medicine, Rajiv Gandhi Institute of Medical Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…Similarly, the prevalence in the current study was also higher than prevalences reported in other countries including Egypt, Kenya, Jordan, and Saudi Arabia where the prevalences were found to be 1.2%, 4.6%, 2.05%, and 3.3%, respectively [2427]. However, the finding of this study is comparable to studies done in India, Ethiopia, and Tanzania, where the prevalences were found to be 14%, 14.8%, and 15%, respectively [2830]. This wide variation in the prevalences of foot ulcers could be due to differences in subject characteristics and the methodology used.…”
Section: Resultssupporting
confidence: 46%
“…Similarly, the prevalence in the current study was also higher than prevalences reported in other countries including Egypt, Kenya, Jordan, and Saudi Arabia where the prevalences were found to be 1.2%, 4.6%, 2.05%, and 3.3%, respectively [2427]. However, the finding of this study is comparable to studies done in India, Ethiopia, and Tanzania, where the prevalences were found to be 14%, 14.8%, and 15%, respectively [2830]. This wide variation in the prevalences of foot ulcers could be due to differences in subject characteristics and the methodology used.…”
Section: Resultssupporting
confidence: 46%